2019
DOI: 10.1021/acschemneuro.9b00305
|View full text |Cite
|
Sign up to set email alerts
|

6-Monoacetylmorphine (6-MAM), Not Morphine, Is Responsible for the Rapid Neural Effects Induced by Intravenous Heroin

Abstract: Heroin rapidly enters the CNS but is quickly metabolized into 6monoacetylmorphine (6-MAM) and then morphine. Although morphine is often thought to mediate heroin's neural effects, pharmacokinetic data question this view. To further understand the effects of heroin and its metabolites, oxygen sensors were used to examine changes in nucleus accumbens (NAc) oxygen levels. Heroin, 6-MAM, and morphine were all administered intravenously at two human-relevant doses (0.25 μmol/kg and 0.98 μmol/kg) in freely moving ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Modelled brain concentrations of heroin, 6-monoacetylmorphine (6-MAM) and morphine (left axis) and cumulative intake (right axis) throughout the 10th heroin self-administration training session of representative rats (infusions: continuous access = 31; intermittent access = 39). Note the scales are adapted to the levels of each compoundGottas et al, 2013;Perekopskiy & Kiyatkin, 2019;Solis et al, 2017)…”
mentioning
confidence: 99%
“…Modelled brain concentrations of heroin, 6-monoacetylmorphine (6-MAM) and morphine (left axis) and cumulative intake (right axis) throughout the 10th heroin self-administration training session of representative rats (infusions: continuous access = 31; intermittent access = 39). Note the scales are adapted to the levels of each compoundGottas et al, 2013;Perekopskiy & Kiyatkin, 2019;Solis et al, 2017)…”
mentioning
confidence: 99%
“…Interestingly, mAb 4G12 only showed significance in tail flick tests starting at 45 min postdrug exposure but was able to bring mice back to baseline faster than controls, similar to 11D12 (Figure b). These results further reinforce the simple antinociception data, vide supra , wherein an antibody targeting heroin is important for early intervention rather than 6-AM, which has been considered the main active metabolite of interest to inhibit for effective therapeutic effects. ,, …”
Section: Resultsmentioning
confidence: 99%
“…These results further reinforce the simple antinociception data, vide supra, wherein an antibody targeting heroin is important for early intervention rather than 6-AM, which has been considered the main active metabolite of interest to inhibit for effective therapeutic effects. 21,29,38 Pharmacokinetics. To observe how the selected mAbs alter heroin's metabolism in vivo, we conducted pharmacokinetic studies by injecting nai ̈ve mice IV with either drug, mAb, or drug and mAb.…”
Section: Monoclonal Antibody Development and Selectionmentioning
confidence: 99%
“…Antidrug vaccines have been investigated for cocaine, nicotine, methamphetamine, , and opioids, and while created in many formats, their overall success still depends upon three components: carrier protein (T-cell epitope), adjuvant, and hapten . With the opioid crisis in full view, opioid vaccines have taken center stage including heroin vaccines that have undergone extensive examination. Although success has been claimed with several heroin vaccines, our continued efforts to rationally design suitable heroin-hapten-drug candidates that are complementary to our pre-existing vaccine arsenal is equally important.…”
mentioning
confidence: 99%
“…Heroin is sequentially metabolized into 6-monoacetylmorphine (6AM) and then to morphine (Figure ), and it is often believed that morphine is responsible for the neural effects of heroin . However, recent assessments have shown that 6-AM is primarily responsible for the rapid effects of this drug, although heroin does possess μ-opioid binding and receptor activation. ,, Constructed upon these criteria, an improved vaccine would be one that could elicit antibodies capable of blocking heroin and its psychoactive metabolites from entering the brain, thereby preventing heroin-induced reinforcement, pharmacokinetics, and locomotor activity. Herein, we detail how hapten deuteration presents a viable tactic that meets these heroin vaccine requirements as observed by titer, specificity, affinity, drug blood–brain distribution, and antinociception evaluation.…”
mentioning
confidence: 99%